Enabling living in space through modern innovations in space medicine: a perspective on tissue-on-a-chip technology - Hazra, Subhajit; Palit, Sibsankar; Russomano, Thais; Ghosh, Gaurab; Sannigrahi, Polash (Frontiers in Space Technologies, 2026)
Human spaceflight has evolved from the short missions of the 1960s to more recent, longer-term missions, such as those aboard the International Space Station (ISS) and future missions to the Moon and Mars. These missions have provided valuable insights into the effects of space-based phenomena, such as microgravity, radiation, and isolation, on human physiology. Studies have shown that microgravity causes rapid muscle atrophy (up to 20% in 1–2 weeks) and bone density loss (1%–1.5% per month), and radiation exposure leads to DNA damage, oxidative stress, and immune suppression. Moreover, immune system dysregulation, evidenced by the reactivation of latent viruses like Epstein-Barr and cytomegalovirus, poses significant health risks. Recent advancements in Tissue-on-a-Chip (ToC) technology offer a promising approach to model immune responses in space, enabling real-time monitoring and testing of countermeasures. Ongoing studies, such as the Tissue Chips in Space Initiative, aim to investigate immune responses under microgravity, focusing on the differentiation of immune cells and the effects of space stressors on immune function. These innovations, including wearable biosensors, are paving the way for a personalized approach to astronaut health monitoring due to their potential applications in both space missions and terrestrial healthcare. Future research must address the scalability, cost-effectiveness, and regulatory standards of ToC technology to ensure its integration in long-duration space missions.